Arktisk råds rolle i polarpolitikken - Pedersen, Torbjørn (Nordlit, 2012)
This article discusses what role(s) member governments want the Arctic Council to have in Arctic affairs. It compares the foreign policies of the five littoral states of the Arctic Ocean: Canada, Denmark, Norway, Russia, and the United States. It identifies and examines three determining debates on a ministerial level over the Arctic Council and the issues it might address: The first debate preceded the Arctic Council's creation in 1996; the second thrived as the five Arctic littoral states convened in Ilulissat, Greenland in 2008; and the third followed a political shift inthe United States in 2009.